Assessment of Potential Companies Based on Performance and Financial Component under Conditions of New Economic Growth Model - Alikaeva, Madina V.; Novoselova, Natalya N.; Kaziyeva, Bella V.; Gurfova, Rita V.; Kerefova, Lidiya Z. G. (International Journal of Economics and Financial Issues, 2016)
In the article there are presented the features of the components that make up the economic capacity of the organization, improve the ability to deepen the analysis of their impact on the effectiveness of and prospects for stable development of the business entity in the new paradigm of economic development. Also, it the authors have developed the technique of evaluating the economic potential of the entertainment, through the application of the component approach and integrated rating. The complex analysis of the economic potential of "Istochnik" based on the proposed method of scoring production and financial potential of the company. Keywords: Economic potential, financial strength, system, production, finance, numerical score, a technique JEL Classification: O18